Optical Photothermal Infrared Microspectroscopy with Simultaneous Raman – A New Non-Contact Failure Analysis Technique for Identification of <10 μm Organic Contamination in the Hard Drive and other Electronics Industries. (May 2020) - Kansiz, Mustafa; Prater, Craig; Dillon, Eoghan; Lo, Michael; Anderson, Jay; Marcott, Curtis; Demissie, Abel; Chen, Yanling; Kunkel, Gary
Abstract: Abstract : Optical Photothermal Infrared (O-PTIR) spectroscopy is a new technique for measuring submicron spatial resolution IR spectra with little or no sample preparation. This speeds up analysis times benefiting high-volume manufacturers through gaining insight into process contamination that occurs during development and on production lines. The ability to rapidly obtain far-field non-contact IR spectra at high spatial resolution facilitates the chemical identification of small organic contaminants that are not possible to measure with conventional Fourier transform infrared (FT-IR) microspectroscopy. The unique pump-probe system architecture also facilitates submicron simultaneous IR + Raman microscopy from the same spot with the same spatial resolution. With these unique capabilities, O-PTIR is finding utilization in the high-volume and high-value industries of high-tech componentry (memory storage, electronics, displays, etc.).